2009
DOI: 10.2298/vsp0909758p
|View full text |Cite
|
Sign up to set email alerts
|

Acute glyphosate-surfactant poisoning with neurological sequels and fatal outcome

Abstract: The outcome of reported poisoning may be the consequence of glyphosate-surfactant neurotoxic effect or/and ischemia, especially in the episodes of marked hypotension during hemodialysis. Considering recommendation of early hemodialysis as the treatment of choice, even before renal failure development, we point out the importance of careful planning of dialysis modality in hemodynamically instable patient and recommend continuous dialysis methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…[ 5 ] In a single case report, patient developed neurotoxic sequels of GlySH-surfactant exposure with white matter lesions and development of Parkinsonism. [ 6 ] Our patient had oral ulcers, gastrointestinal involvement, and deteriorated due to development of acute pulmonary edema and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] In a single case report, patient developed neurotoxic sequels of GlySH-surfactant exposure with white matter lesions and development of Parkinsonism. [ 6 ] Our patient had oral ulcers, gastrointestinal involvement, and deteriorated due to development of acute pulmonary edema and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CBZ level was assessed using a biochemical auto analyzer (ARCHITECT c8000 Clinical Chemistry analyzer, Abbott®, U.S., Japan). Total oxidative status (TOS) ( 9 ) and TAS of serum was determined using a novel automated measurement method developed by Erel ( 10 , 11 ). Oxidants present in the sample oxidize the ferrous ion-o-dianisidine complex to ferric ion.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, malondialdehyde (MDA) values, an indicator of membrane lipid peroxidation, were found to be unchanged in children with epilepsy ( 8 ). Oxidative stress index ( 9 ) is reported as a valuable parameter indicating oxidative stress level. Furthermore, previously conducted studies revealed that oxidative stress index (OSI) rate indicates oxidative injury, as well ( 10 - 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical picture of severe GI poisoning may result in some clinical complications such as gastroenteritis, respiratory diseases, alterations in mental status, nephrotoxicity, acute renal failure, shock, neurological sequel, and death. 4,5…”
Section: Introductionmentioning
confidence: 99%